2020
DOI: 10.21776/ub.jkb.2020.031.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lamina Papyracea Area and Ethmoid Sinus Volume in Indonesian Patients Undergoing Paranasal Sinus CT Scan

Abstract: Of the rhinosinusitis (CRS) patients, half of whom require surgical intervention. Functional endoscopic sinus surgery (FESS) is a standard treatment of CRS and sinonasal polyposis. Orbito-ocular complications can occur during FESS. The lamina papyracea (LP) is the weakest point of the medial wall of the orbit. The variability in the size and shape of the paranasal sinuses is important in the FESS procedure. The ethmoid sinus is the most complex paranasal sinuses. Preoperative evaluation using computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The study by Nitin et al also found that the maxillary sinus (68.03%) was the most frequently affected sinus, followed by anterior ethmoid sinusitis (60.66%) [14]. Wahyuni's study showed a correlation between age and height of the left posterior papiracea (p=0.02), but there was no correlation between ethmoid sinus volume and age [15].…”
Section: Discussionmentioning
confidence: 97%
“…The study by Nitin et al also found that the maxillary sinus (68.03%) was the most frequently affected sinus, followed by anterior ethmoid sinusitis (60.66%) [14]. Wahyuni's study showed a correlation between age and height of the left posterior papiracea (p=0.02), but there was no correlation between ethmoid sinus volume and age [15].…”
Section: Discussionmentioning
confidence: 97%